2011
DOI: 10.1152/ajpheart.01127.2010
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian enabled (Mena) is a critical regulator of cardiac function

Abstract: Mammalian enabled (Mena) of the Drosophila enabled/vasodilator-stimulated phosphoprotein gene family is a cytoskeletal protein implicated in actin regulation and cell motility. Cardiac Mena expression is enriched in intercalated discs (ICD), the critical intercellular communication nexus between adjacent muscle cells. We previously identified Mena gene expression to be a key predictor of human and murine heart failure (HF). To determine the in vivo function of Mena in the heart, we assessed Mena protein expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…However, YY1 over-expression results in cardiac dysfunction and activation of the pathologic gene program in males but not in females. Previous work has shown that YY1 increases activity of the androgen receptor [13] , and increased expression of the androgen receptor results in higher Mena levels [14], a protein highly expressed in human and animal models of heart failure [15]. We show that Mena levels are higher in the failing male human heart and YY1-transgenic mouse males, but not in the failing female human heart or female YY1-transgenic mice.…”
Section: Introductionmentioning
confidence: 48%
See 2 more Smart Citations
“…However, YY1 over-expression results in cardiac dysfunction and activation of the pathologic gene program in males but not in females. Previous work has shown that YY1 increases activity of the androgen receptor [13] , and increased expression of the androgen receptor results in higher Mena levels [14], a protein highly expressed in human and animal models of heart failure [15]. We show that Mena levels are higher in the failing male human heart and YY1-transgenic mouse males, but not in the failing female human heart or female YY1-transgenic mice.…”
Section: Introductionmentioning
confidence: 48%
“…YY1 has been shown to potentiate the transcriptional activity of the androgen receptor [13], and transgenic mice over-expressing the androgen receptor have increased expression of mammalian enabled (Mena) [14], a factor that regulates cytoskeletal actin dynamics and whose expression is increased in several models of cardiac pathology [15]. As shown in Figure 3A, Mena expression is higher in male but not female YY1 transgenic mice than transgenic negative controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, these genes have also been previously linked to dilated cardiomyopathy (Aguilar et al, 2011; Bienengraeber et al, 2004; Gehmlich et al, 2007; Yung et al, 2004). …”
Section: Resultsmentioning
confidence: 99%
“…Similar to studies related to breast tumor cell cultures, in case of cardiac embryogenesis, VASP, Mena, and E-cadherin were colocalized in the intercalated disk, and the authors suggested that Mena could not only be implied in actin remodeling but also in intercellular communication [24, 29]. This role was also proved in the adult knockout mice Mena−/− that presented low levels of vinculin, another adherence junction protein, when compared with the wild-type mice [30]. …”
Section: Mena Expression In Nontumor Premalignant and Malignant mentioning
confidence: 99%